MEMANFAATKAN PERKEMBANGAN TEKNOLOGI INTERNET DAN SITUS WEB UNTUK KEPENTINGAN WARGA SEKALIGUS SEBAGAI SARANA PROMOSI POTENSI DESA GERBOSARI - Fajar Hidayanto (Asian Journal of Innovation and Entrepreneurship, 2015)
Web page is the building blocks of websites, are documents, typically composed inplain text interspersed with formatting instructions of Hypertext Markup Language(HTML, XHTML). Those plain text are then connected to a web server that can beaccessed over a network such as the Internet, or a local area network (LAN) via theInternet addresses known as URL. By being in a web server, a website will be freelyaccessible to everyone. Freedom of access makes the website become the bestpromotional media today. Wide coverage into people is another reason to select awebsite as a media campaign. Desa Gerbosari which has many potential should be ableto take advantage of the website as media promotion. With the web site of the villageand community and village officials who are able to manage, Desa Gerbosari’s potentialwill be well-publicized and attract tourists.